THE INFLUENCE OF ONLINE CUSTOMER RATINGS, ONLINE CUSTOMER REVIEWS, AND PRICE PERCEPTIONS ON PURCHASING DECISIONS IN SHOPEE E-COMMERCE (Study on FEB Management Students Universitas Malikussaleh) - Adnan; Rusydi Abubakar; Heriyana; Andri Ani Nur (RADJA PUBLIKA, 2024)
The research aims to determine how online customer ratings, online customer reviews, and price perceptions influence purchasing decisions on Shopee e-commerce among Management students of FEB Universitas Malikussaleh class of 2020. The data used in this research is primary data obtained by distributing questionnaires online and directly to students who use Shopee e-commerce. The sample in this research consists of 140 respondents using a non-probability sampling technique, namely purposive sampling. This research employs multiple linear regression analysis using SPSS software version 25. The results show that partially, online customer ratings, online customer reviews, and price perceptions have a positive and significant effect on purchasing decisions. Meanwhile, the simultaneous test results show that online customer ratings, online customer reviews, and price perceptions have a positive and significant effect on the Management students of FEB Universitas Malikussaleh class of 2020. The coefficient of determination test results indicate that purchasing decisions on Shopee e-commerce are influenced by online customer ratings, online customer reviews, and price perceptions by 42.8%, while the remaining 57.2% is influenced by variables outside this research.